2020
DOI: 10.1002/eat.23358
|View full text |Cite
|
Sign up to set email alerts
|

Identifying research priorities for the study of atypical anorexia nervosa: A Delphi study

Abstract: Objective: Individuals meeting all criteria for anorexia nervosa (AN) except that weight falls within or above the normal range despite significant weight loss are categorized as having atypical AN (AAN). Existing research has provided mixed evidence concerning the diagnostic demarcation of AN and AAN. The aim of the present study was to identify research priorities for furthering the understanding of AN and AAN as diagnostic entities. Method: Employing the Delphi methodology, experts in the field were invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
17
1
Order By: Relevance
“…Data on participants’ self-admission episodes and number of participants in the program were retrieved from patient records. In sum, the cohort study on which the present analysis is based showed a statistically significant ( p = .001) 51.1 % reduction in time spent hospitalized (at SCÄ and all other Swedish health services) at one-year follow-up, compared to a statistically non-significant ( p = .259) 34.7 % increase in the TAU comparison group [ 13 ]. However, participants’ BMI or eating disorder morbidity was not affected in a clinically meaningful way during follow-up and HRQoL outcomes were inconclusive.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Data on participants’ self-admission episodes and number of participants in the program were retrieved from patient records. In sum, the cohort study on which the present analysis is based showed a statistically significant ( p = .001) 51.1 % reduction in time spent hospitalized (at SCÄ and all other Swedish health services) at one-year follow-up, compared to a statistically non-significant ( p = .259) 34.7 % increase in the TAU comparison group [ 13 ]. However, participants’ BMI or eating disorder morbidity was not affected in a clinically meaningful way during follow-up and HRQoL outcomes were inconclusive.…”
Section: Methodsmentioning
confidence: 88%
“…Available findings indicate that being offered self-admission as a tool in the treatment of eating disorders helped participants prevent deterioration and reduce their need for inpatient treatment, but that it did not aid in achieving symptom remission such as a normalized weight or reduced eating disorder cognitions [ 13 ]. Considering that the targeted participant group displayed a mean duration of illness of 13.4 years, self-admission certainly should not be expected to provide a “quick fix”.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations